Brownfield regeneration: Towards strengthening social cohesion? - Minić, Marta; Perić, Ana (Arhitektura i urbanizam, 2016)
In broader terms, the paper refers to the topic of brownfield regeneration, as one of the most complex mechanisms for sustainable spatial development. In addition to the fact that brownfield regeneration demands a variety of instruments, such as: tax subsidies, the change of land use ownership, soil remediation, planning regulative ammendments, etc., the complexity of brownfield regeneration is primarily seen in a great number of stakeholders participating in such a process. Thus, the paper focuses on the social aspect of brownfield regeneration – precisely, on researching the community role and reviewing the possiblities for achieving the ’local’ interests in complex developmental processes. The main research hypothesis is that brownfield regeneration positively affects the creation and strengthening of social cohesion in the areas close to the brownfield site. The thesis is examined by two main parameters: 1) participation of local community, and 2) social costs and benefits of brownfield regeneration versus greenfield investment. The research results are presented in the form of argumentative essay. In fact, the critical overview of arguments for and against the main research hypothesis is provided based on the review of interdisciplinary literature in the domain of brownfield regeneration. Such research organisation ensures the identification and description of the measures needed for strengthening social cohesion, as an utmost goal of this research. The final research contribution is about offering the guidelines for similar methodological approach in urban research. Keywords: urban regeneration, brownfields, social cohesion, sustainable development